2016
DOI: 10.1063/1.4940382
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoelectric effect in negative magnetostrictive/piezoelectric/positive magnetostrictive semiring structure

Abstract: Magnetoelectric (ME) Ni/PZT/TbFe2 and TbFe2/PZT composites with two semiring structures are prepared. The dependence between ME coupling and magnetostrictive property of the composite is discussed. Because Ni possesses negative magnetostrictive property and TbFe2 shows positive magnetostrictive property, the ME voltage coefficient of Ni/PZT/TbFe2 semiring structure is much larger than that of TbFe2/PZT. In these composites, the ME voltage coefficient increases and the resonance frequency gradually decreases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In 2016 [ 35 ], a giant ME effect was obtained in negative magnetostrictive/piezoelectric/positive magnetostrictive semiring structure ( Figure 5 ). The research team managed to significantly reduce the bias field to 240 Oe, while maintaining the sensor sensitivity of 10 −12 T and a low noise level of 2 × 10 −12 T/Hz 1/2 , as well as to obtain a giant ME voltage coefficient for structures based on Terfenol-D 44.8 V cm −1 ∙Oe −1 .…”
Section: Main Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016 [ 35 ], a giant ME effect was obtained in negative magnetostrictive/piezoelectric/positive magnetostrictive semiring structure ( Figure 5 ). The research team managed to significantly reduce the bias field to 240 Oe, while maintaining the sensor sensitivity of 10 −12 T and a low noise level of 2 × 10 −12 T/Hz 1/2 , as well as to obtain a giant ME voltage coefficient for structures based on Terfenol-D 44.8 V cm −1 ∙Oe −1 .…”
Section: Main Sectionmentioning
confidence: 99%
“…It can be seen that different research groups used separate types of composite structures (disc-shaped, rectangular, etc.). The most promising is a magnetic field sensor based on a negative magnetostrictive/piezoelectric/positive magnetostrictive semiring structure [ 35 ]. The magnitude of the ME coefficient in terms of voltage in this sensor reached values α E = 44.8 V∙cm −1 ∙Oe −1 , with relatively identical values of sensitivity and noise level.…”
Section: Main Sectionmentioning
confidence: 99%
“…Because the elongation of the ferroelectric layer is not directly produced by the applied electric field but instead driven by the ferromagnetic layer, the interface coupling between the two phases becomes the key factor for an enhanced ME effect [34]. In order to reduce the influence of interface properties on the magnetoelectric response, many novel magnetoelectric structures are designed and prepared [34,35,36,37,38,39]. For example, Bi et al made the magnetic material into a groove and placed the piezoelectric layer in the groove.…”
Section: Introductionmentioning
confidence: 99%
“…This design makes the stress transfer between the magnetostrictive layer and the piezoelectric layer no longer dependent on the interface layer, avoiding the influence of the interface layer on the magnetoelectric response [36]. Zeng et al reported a giant magnetoelectric effect in negative magnetostrictive/piezoelectric/positive magnetostrictive semiring structures, with the maximal ME coefficient at 56.3 V/A [38]. Wen et al presented a novel ME structure, made up of one Terfenol-D layer and three PZT-5A layers, and showed that the three PZT-5A layers can be driven by one Terfenol-D layer simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only a very limited number of singlephase oxides, such as Cr 2 O 3 , YMnO 3 , BiFeO 3 , BiMnO 3 , RMnO 3 and RMn 2 O 5 (R: rare earth), have been reported to exhibit multiferroic phenomena. Due to the limited availability of single-phase multiferroics and their usually weak coupling effect, recent efforts have been directed toward production of multiferroic composites [1][2][3][4]. In such composites, the response of the magnetic (or electric) phase under a magnetic (or electric) field can be transmitted to the electric (or magnetic) phase through their common elastic deformation, leading to the ME coupling [5,6].…”
Section: Introductionmentioning
confidence: 99%